College Algebra (11th Edition)

Published by Pearson
ISBN 10: 0321671791
ISBN 13: 978-0-32167-179-0

Chapter R - Section R.3 - Polynomials - R.3 Exercises: 16

Answer

-8$y^{12}$

Work Step by Step

-$(2x^{0}y^{4})^{3}$ = -$(2^{3})$$(x^{0})^{3}$$(y^{4})^{3}$ = -$(2^{3})$$x^{0*3}$$y^{4*3}$ = -8$x^{0}$$y^{12}$ = -8(1)($y^{12}$) = -8$y^{12}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.